(untitled) (Malaysian Journal of Civil Engineering, 2018)
In this study, effects of hydraulic retention time (HRT) and influent COD concentration on biological nutrient removal and changes in microbial community structure in an Membrane bioreactor (MBR) based system were investigated. Three different levels of CODinf and three HRTs (4, 5 & 8 hrs) were applied. Total nitrogen and total phosphorus removal efficiencies were 74% and 89%, respectively when high CODin was supplied to the MBRs. The comparison of microbial community structure between the sludges from the MBR performing poor biological phosphorus removal and from the MBR demonstrating enhanced phosphorus removal pointed out that microorganisms containing ubiquinone UQ-9, and menaquinone MK-7, -8(H2), -9(H4) and -10 (H4) were responsible for improvement in treatment efficiencies. The analysis of microbial community structure indicated that subclass ï§- Proteobacteria, species of the genera Rhodoccocus, members of the genus Gordonia and Microlunatus phosphovorus can be considered potential phosphate accumulating organisms in the MBR.